Numerical solution and stability analysis of non-Newtonian hybrid nanofluid flow subject to exponential heat source/sink over a Riga sheet - Yasmin Humaira; Bossly Rawan; Alduais Fuad S.; Al-Bossly Afrah; Saeed Anwar (Open Physics)
The non-Newtonian (NN) hybrid nanofluids (HNF) flow over a porous stretching or shrinking Riga sheet is calculated. The HNF is produced by the scattering of cerium oxide (CeO2) and aluminum oxide (Al2O3) nanoparticles. NN HNF offers a wide variety of uses. For instance, enhanced heat transportation, cooling, maintenance, and reliability in mechanically powered delivery of medicines, increased efficacy in microfluidic devices, advanced material synthesis, and energy-related applications such as storing energy and solar power generation systems are a few of them. For this purpose, the flow phenomena are modeled in the form of nonlinear partial differential equations (PDEs), which are reduced into the dimension-free form through the similarity conversion. The solution is obtained by using the numerical approach parametric continuation method. The stability analysis has also been performed to check which solution is stable and reliable in practice. The results are compared to the numerical outcomes of the published studies. The present findings have shown the best correlation with the previous published studies. The relative error between the published and present study at Pr = 10 (Prandtl number) is 0.00046%, which is gradually reduced up to 0.00202% with the variation of Pr = 0.7. Furthermore, the impact of a viscoelastic factor enhances the velocity field of HNF (Al2O3 and CeO2/SA) for both types of NN fluids (second-grade fluid & Walter’s B fluid) in the case of stretching Riga sheet.